Banana Fusarium wilt management: towards sustainable cultivation: Proceedings of the International workshop on the banana fusarium wilt disease, Genting Highlands resort, Malaysia, 18-20 october 1999 - Molina, A.B.; Nik Masdek, N.H.; Liew, K.W. (2001)
Fusarium wilt is one of the most devastating banana diseases at the global level and is the number one constraint to banana production in Asia. A first international conference on Fusarium wilt was held in Miami in 1989, and this resulted in the publication of a book entitled 'Fusarium wilt of Banana'. Since then, many developments have taken place. Research has made significant progress, especially in the development and release of resistant varieties, and in the biochemical and molecular characteriszation of Fusarium strains. A second International workshop was therefore organized in 1999 in order to review the current status of Fusarium wilt disease on bananas and identify priorities for future research. The proceedings of this workshop include scientific papers from the banana world's Fusarium wilt specialists covering the themes of pathogen diversity; monitoring and screening methodology; varietal improvement; and disease management. The publication also contains country reports from Asia, the Pacific, Africa and Latin America.